De-escalating adjuvant therapies in older patients with lower risk estrogen receptor-positive breast cancer treated with breast-conserving surgery: A systematic review and meta-analysis. (September 2021) - Savard, Marie-France; Clemons, Mark; Hutton, Brian; Jemaan Alzahrani, Meshari; Caudrelier, Jean-Michel; Vandermeer, Lisa; Liu, Michelle; Saunders, Deanna; Sienkiewicz, Marta; Stober, Carol; Cole, Katherine; Shorr, Risa; et al.
Highlights: Older adults with low risk breast cancer might not benefit from adjuvant therapies. This systematic review evaluates data on the omission of endocrine and radiation therapies. Radiation therapy prevents local breast cancer recurrence without improving survival. Trials are needed on the omission of endocrine therapy for lower risk breast cancer. Abstract: Purpose: Radiation therapy (RT) and endocrine therapy (ET) are standard treatments for hormone receptor-positive (HR+) breast cancer after breast-conserving surgery (BCS). However, many older patients are at greater risk of treatment-related toxicities and non-cancer related death, and less likely to benefit from these standard treatments. A systematic review was performed evaluating outcomes of omitting RT or ET in older patients aged ≥50 treated with BCS for lower-risk breast cancer. Methods: Medline, Embase, and the Cochrane Register of Controlled Trials were queried from 1980 to April 30th, 2020 for randomized controlled studies (RCTs) and prospective cohort studies (PCSs) evaluating omission of RT and/or ET compared to RT plus ET in patients. Meta-analysis was performed using random-effects models with findings reported as risk ratios (RR) with 95% confidence intervals (CI). Results: From 3860 citations, 10 prospective studies met eligibility criteria. Omission of RT alone was evaluated in 7 RCTs (n = 4604) and one PCS (n = 667); omission of ET alone was assessed in 1 PCS (n = 271); and omission of either ET or RT was compared to ET plus RT in 1 RCT (n = 495). Adjuvant RT compared to no RT reduced 5- and 10-year in-breast tumor recurrence [5-year: RR 0.16, 95 %CI 0.09–0.27 l 10-year: 0.28, 95 %CI 0.16–0.5], but had no effect on survival [5-year: RR 0.94, 95 %CI 0.77–1.15; 10-year: 1.01, 95 %CI 0.9–1.12]. Conclusion: The current body of evidence suggests that RT can be omitted in older patients with lower-risk disease. However, more trials on the omission of ET are required to better inform treatment decisions.